Safety and Pharmacokinetics of Oral Cannabidiol When Administered Concomitantly With Intravenous Fentanyl in Humans. Issue 3 (May 2015) - Manini, Alex F.; Yiannoulos, Georgia; Bergamaschi, Mateus M.; Hernandez, Stephanie; Olmedo, Ruben; Barnes, Allan J.; Winkel, Gary; Sinha, Rajita; Jutras-Aswad, Didier; Huestis, Marilyn A.; Hurd, Yasmin L.
<x xml:space="preserve">Abstract</x> Objectives: Cannabidiol (CBD) is hypothesized as a potential treatment for opioid addiction, with safety studies an important first step for medication development. We determined CBD safety and pharmacokinetics when administered concomitantly with a high-potency opioid in healthy subjects. Methods: This double-blind, placebo-controlled cross-over study of CBD, coadministered with intravenous fentanyl, was conducted at the Clinical Research Center in Mount Sinai Hospital, a tertiary care medical center in New York City. Participants were healthy volunteers aged 21 to 65 years with prior opioid exposure, regardless of the route. Blood samples were obtained before and after 400 or 800 mg of CBD pretreatment, followed by a single 0.5 (session 1) or 1.0 μg/kg (session 2) of intravenous fentanyl dose. The primary outcome was the Systematic Assessment for Treatment Emergent Events (SAFTEE) to assess safety and adverse effects. CBD peak plasma concentrations, time to reach peak plasma concentrations (tmax), and area under the curve (AUC) were measured. Results: SAFTEE data were similar between groups without respiratory depression or cardiovascular complications during any test session. After low-dose CBD, tmax occurred at 3 and 1.5 hours in sessions 1 and 2, respectively. After high-dose CBD, tmax occurred at 3 and 4 hours in sessions 1 and 2, respectively. There were no significant differences in plasma CBD or cortisol (AUC P = NS) between sessions. Conclusions: Cannabidiol does not exacerbate adverse effects associated with intravenous fentanyl administration. Coadministration of CBD and opioids was safe and well tolerated. These data provide the foundation for future studies examining CBD as a potential treatment for opioid abuse.